Effectiveness of an electronic hand hygiene monitoring system on healthcare workers' compliance to guidelines - J.M. Al Salman; S. Hani; N. de Marcellis-Warin; Sister Fatima Isa (Elsevier, 2015)
Summary: Hand hygiene is a growing concern among populations and is a crucial element in ensuring patient safety in a healthcare environment. Numerous management efforts have been conducted in that regard, including education, awareness and observations. To better evaluate the possible impact of technology on a healthcare setting, we observed the impact of a particular niche technology developed as an answer to the growing hand hygiene concerns. A study was conducted at Salmaniya Medical Complex (SMC) in Bahrain on a total of 16 Coronary Care Unit (CCU) beds where the system was installed, and the hand hygiene activity of healthcare workers (HCWs) in this area was monitored for a total period of 28 days. Comments, remarks and suggestions were noted, and improvements were made to the technology during the course of the trial. While resistance to change was significant, overall results were satisfactory. Compliance with hand hygiene techniques went from 38-42% to 60% at the beginning of the trial and then increased to an average of 75% at the end of the 28-day trial. In some cases, compliance peaked at 85% or even at 100%. Our case study demonstrates that technology can be used effectively in promoting and improving hand hygiene compliance in hospitals, which is one way to prevent cross-infections, especially in critical care areas. Keywords: Hand hygiene compliance, Healthcare technology, Resistance to change